The drooling reduction intervention trial (DRI): a single blind trial comparing the efficacy of glycopyrronium and hyoscine on drooling in children with neurodisability - Parr, Jeremy R (BioMed Central, 2014)
BACKGROUND: Drooling saliva is a common problem in children with neurodevelopmental disorders. The negative consequences of drooling include skin breakdown, dehydration, and damage to clothing and equipment. Children and families often suffer social embarrassment due to drooling. There is no evidence about the relative effectiveness, side effect profiles or patient acceptability of the two medications most commonly used to reduce drooling - glycopyrronium and hyoscine. Consequently, there is no consensus or guideline to aid clinical decisions about which drug to use, and at what dose. METHODS/DESIGN: A multi-centre, randomised trial of treatment with glycopyrronium or hyoscine in children with problematic drooling and non-progressive neurodisability. Ninety children aged between 3 and 15 years who have never received medication for drooling will be stratified by severity of drooling and care centre. Randomisation to receive treatment with glycopyrronium or hyoscine will be computer generated from the trial randomisation website. Dose adjustment and side effect monitoring will occur via telephone consultation. Medication arm will be known to participants and clinicians but not the Trial Outcome Assessor. The primary outcome measure is the Drooling Impact Scale score at four weeks, at which time all children will be on the maximum tolerated dose of their medication. Secondary outcome measures include change in Drooling Impact Scale score between baseline, 4, 12 and 52 weeks, change in Drooling Severity and Frequency Scale score and difference between groups in the Treatment Satisfaction Questionnaire for Medication score. A structured interview with children and young people of sufficient age, cognitive and communication ability will explore their perceptions of drooling and the effectiveness and acceptability of the medications. DISCUSSION: The primary objective of the study is to identify whether glycopyrronium or hyoscine is more effective in treating drooling in children with non-progressive neurodisability. The study will also determine which medications at what doses are most acceptable and have fewest side effects. This information will be used to develop evidence based guidance to inform the medical treatment of drooling. DRI TRIAL REGISTRATION: Current Controlled Trials: ISRCTN75287237. EUDRACT: 2013-000863-94. Medicines and Healthcare products Regulatory Agency (MHRA): 17136/0264/001-0003.